Pathogenicity and Immune Response Measured in Mice following Intranasal Challenge with Enterotoxigenic Escherichia coli Strains H10407 and B7A - Byrd, Wyatt (American Society for Microbiology, 2003)
The pathogenicity and immunogenicity induced in BALB/c mice by intranasal (i.n.) inoculation of enterotoxigenic Escherichia coli (ETEC) strains H10407 (O78:H11:CFA/I:LT(+):ST(+)) and B7A (O148:H28:CS6:LT(+):ST(+)) (two ETEC strains previously used in human challenge trials) were studied. The i.n. inoculation of BALB/c mice with large doses of ETEC strains H10407 and B7A caused illness and death. The H10407 strain was found to be consistently more virulent than the B7A strain. Following i.n. challenge with nonlethal doses of H10407 and B7A, the bacteria were cleared from the lungs of the mice at a steady rate over a 2-week period. Macrophages and neutrophils were observed in the alveoli and bronchioles, and lymphocytes were observed in the septa, around vessels, and in the pleura of the lungs in mice challenged with H10407 and B7A. In mice i.n. challenged with H10407, serum immunoglobulin G (IgG) and IgM antibodies were measured at high titers to the CFA/I and O78 lipopolysaccharide (LPS) antigens. In mice i.n. challenged with B7A, low serum IgG antibody titers were detected against CS6, and low serum IgG and IgM antibody titers were detected against O148 LPS. The serum IgG and IgM antibody titers against the heat-labile enterotoxin were equivalent in the H10407- and B7A-challenged mice. The CFA/I and O78 LPS antigens gave mixed T-helper cell 1-T-helper cell 2 (Th1-Th2) responses in which the Th2 response was greater than the Th1 response (i.e., stimulated primarily an antibody response). These studies indicate that the i.n. challenge of BALB/c mice with ETEC strains may provide a useful animal model to better understand the immunogenicity and pathogenicity of ETEC and its virulence determinants. This model may also be useful in providing selection criteria for vaccine candidates for use in primate and human trials.